2013
DOI: 10.1002/wrcr.20292
|View full text |Cite
|
Sign up to set email alerts
|

Potential climate change effects on groundwater recharge in the High Plains Aquifer, USA

Abstract: [1] Considering that past climate changes have significantly impacted groundwater resources, quantitative predictions of climate change effects on groundwater recharge may be valuable for effective management of future water resources. This study used 16 global climate models (GCMs) and three global warming scenarios to investigate changes in groundwater recharge rates for a 2050 climate relative to a 1990 climate in the U.S. High Plains region. Groundwater recharge was modeled using the Soil-Vegetation-Atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 62 publications
8
147
2
4
Order By: Relevance
“…Because of the large discrepancy between these two GR p datasets, we opted to use a modified "Delta" method implemented by the U.S. Bureau of Reclamation (USBR, 2010), and follow the approach similar to Crosbie et al (2013) in presenting future climate change results as changes in GR p . With this method, adjustments are made to the modern period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) GR p,MODIS rates based on relative changes projected by the CMIP3/VIC scenarios as recharge scaling factors (RSFs).…”
Section: Future Periodmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the large discrepancy between these two GR p datasets, we opted to use a modified "Delta" method implemented by the U.S. Bureau of Reclamation (USBR, 2010), and follow the approach similar to Crosbie et al (2013) in presenting future climate change results as changes in GR p . With this method, adjustments are made to the modern period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) GR p,MODIS rates based on relative changes projected by the CMIP3/VIC scenarios as recharge scaling factors (RSFs).…”
Section: Future Periodmentioning
confidence: 99%
“…Thus, interest in this topic has increased greatly over recent years (e.g., Crosbie et al, 2013;Ferguson and Maxwell, 2012;Green et al, 2011;Gurdak et al, 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Russell S. Crosbie (2013) concluded that vegetation is not necessarily a strong determinant of the sensitivity of recharge to climate change as sensitivity differs based on the amount of historical baseline recharge and not necessarily vegetation type. Sensitivity of recharge to changes in rainfall is least for high baseline recharge and greatest for low baseline recharge.…”
Section: Waves Model With Improvementsmentioning
confidence: 99%